Bacillus velezensis AP183 Inhibits Staphylococcus aureus Biofilm Formation and Proliferation in Murine and Bovine Disease Models - Afroj, Sayma; Brannen, Andrew D.; Nasrin, Shamima; Al Mouslem, Abdulaziz; Hathcock, Terri; Maxwell, Herris; Rasmussen-Ivey, Cody R.; Sandage, Mary J.; Davis, Edward W.; Panizzi, Peter; Wang, Chengming; Liles, Mark R. (Frontiers in Microbiology, 2021)
The increasing frequency of Staphylococcus aureus antimicrobial resistance has spurred interest in identifying alternative therapeutants. We investigated the S. aureus-inhibitory capacity of Bacillus velezensis strains in mouse and bovine models. Among multiple B. velezensis strains that inhibited S. aureus growth in vitro, B. velezensis AP183 provided the most potent inhibition of S. aureus proliferation and bioluminescence in a mouse cutaneous wound (P = 0.0198). Histology revealed abundant Gram-positive cocci in control wounds that were reduced in B. velezensis AP183-treated tissues. Experiments were then conducted to evaluate the ability of B. velezensis AP183 to prevent S. aureus biofilm formation on a tracheostomy tube substrate. B. velezensis AP183 could form a biofilm on a tracheostomy tube inner cannula substrate, and that this biofilm was antagonistic to S. aureus colonization. B. velezensis AP183 was also observed to inhibit the growth of S. aureus isolates originated from bovine mastitis cases. To evaluate the inflammatory response of mammary tissue to intramammary inoculation with B. velezensis AP183, we used high dose and low dose inocula in dairy cows. At the high dose, a significant increase in somatic cell count (SCC) and clinical mastitis was observed at all post-inoculation time points (P < 0.01), which resolved quickly compared to S. aureus-induced mastitis; in contrast, the lower dose of B. velezensis AP183 resulted in a slight increase of SCC and no clinical mastitis. In a subsequent experiment, all mammary quarters in four cows were induced to have grade 1 clinical mastitis by intramammary inoculation of a S. aureus mastitis isolate; following mastitis induction, eight quarters were treated with B. velezensis AP183 and milk samples were collected from pretreatment and post-treatment samples for nine days. In groups treated with B. velezensis AP183, SCC and abundance of S. aureus decreased with significant reductions in S. aureus after three days post-inoculation with AP183 (P = 0.04). A milk microbiome analysis revealed significant reductions in S. aureus relative abundance in the AP183-treated group by eight days post-inoculation (P = 0.02). These data indicate that B. velezensis AP183 can inhibit S. aureus biofilm formation and its proliferation in murine and bovine disease models.